Learning difficulties in Mathematics: some reflections - Wilson de Jesus Masola; Norma Suely Gomes Allevato (Educação Matemática Debate, 2019)
The purpose of the present paper is to show how some current researches – published in papers and books – approach the difficulties in Mathematics learning. We intend to reflect on teaching and learning Mathematics by analysing some aspects that have been pointed out, especially about learning difficulties some students have in Mathematics area. We used the research qualitative approach with procedures of document analysis. At first, we described the meaning of the word ‘difficulty’, passing through learning difficulties and learning difficulties in Mathematics. The latest researches point the urgent need of a didactic overhaul in Mathematics teaching and maturation of all school communitiy, regardless the teaching level, concerning learning difficulties.